Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan UMK Sektor Perdagangan di Kecamatan Banjarmasin Utara - Munibah, Noor; Chandriyanti, Ika (PPJP ULM, 2023)
This study has the following objectives: 1) to determine the effect of wages, working hours, capital, and education simultaneously on the MSE income in the trading sector in North Banjarmasin District. 2) to determine the effect of wages, working hours, capital, and education partially on MSE income in the trade sector in North Banjarmasin District. In this study, the authors use quantitative methods through a descriptive approach. Primary data types are generated through the distribution of questionnaires and interviews. The analysis technique uses descriptive analysis and multiple linear regression using the Ordinary Least Square (OLS) method. The results of this study reveal that Simultaneously (f test) illustrates that the independent variables X1(Wage), X2(Working Hours), X3(capital), and X4(Education) together simultaneously have a significant effect on Y(Income) in MSEs in the Trade Sector in the District of North Banjarmasin. Partially, the independent variables X1(Wage), X2(Working Hours), and X3(Capital) affect Y(Income), while the X4(Education) variable does not affect Y(Income).